COFFEE CONCENTRATION USING OSMOTIC MEMBRANE DISTILLATION TECHNOLOGY - Fadhia, Najma
Coffee is one of Indonesian exports commodity with high economic value in the global market. Coffee production in Indonesia reached 762 thousand tons in 2020 with productivity of 811 kg/ha. Unfortunately, exports of processed coffee products are still low. One of the processed coffee products that is popular because of its taste, energyboosting effect, and ease of storage is instant coffee. In Indonesia, the trend of coffee consumption is increasing and it is estimated that it will continue to increase up to 3.07%. A crucial step in the production of ground instant coffee is the concentration process. The commonly used coffee concentration methods are evaporation and freeze drying. However, these methods have disadvantages such as the loss of important compounds and the expensive equipment. The technology that is feasible to be used for coffee concentration is osmotic membrane distillation (OMD) technology. The purpose of this study was to concentrate coffee from ground coffee extract using an osmotic distillation membrane. In addition, this study also aims to determine the effect of variations in temperature, flow rate, and concentration of draw solution on the coffee concentration process, and to determine the presence of fouling and wetting phenomena in coffee concentration process using OMD. This research is carried out in the variations of temperature of 40°C and 55°C, draw solution flow rate of 1 ml/s and 1,5 ml/s, and concentration of draw solution in the form of calcium chloride of 2 M and 6 M. The experimental design in this study using a 23 factorial design with three center points. The results of the preliminary experiments show that the three experimental factors affect the permeate flux, therefore these factors are used as the main experimental factors. The main experiment results indicate that temperature has a significant effect on OMD performance and all parameters of coffee quality. Flow rate did not show any significant effect on OMD performance or coffee quality parameters. The concentration of draw solution has a significant effect on the OMD performance and total dissolved solids. The interaction of temperature and concentration of draw solution has a significant effect on OMD performance and total phenolic compound, the interaction of temperature and flow rate has a significant effect on the degree of concentration, and the interaction of the three experimental factors has a significant effect on the degree of coffee concentration. After four hours of concentration, it shows that fouling just began to form and no wetting phenomenon was detected.